(untitled) (Physical Education, Health and Social Sciences, 2026)
This research focuses on how government school teachers view standardized tests and whether they think these tests are in line with the curriculum standards and classroom assessments. Accountability pressure, curriculum test alignment, test, preparation intensity, formative assessment practices, and perceived fairness were measured in a cross, sectional survey of 300 teachers. Descriptive statistics, t, tests for independent samples, one, way ANOVA, and Pearson correlations were used. Teachers indicated moderate accountability and alignment and slightly stronger formative practices. No significant differences between genders were found. The comparisons of urban rural revealed small but statistically significant differences in test preparation, formative practice, and fairness, while school level differences were only for fairness. Teaching experience was a significant predictor of formative assessment, where teachers with 11+ years scored higher than those with 05 years. The correlations between constructs were weak and negative, which indicates trade, offs between test preparation and formative routines. The internal consistency estimates were very low, suggesting item, coding problems and the necessity for further psychometric validation. The findings encourage the transition to balanced assessment systems and the development of teacher’s assessment literacy as a means of better safeguarding learning and equity.